2014
DOI: 10.2478/popore-2014-0026
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of moss dwelling ciliates from King George Island, Antarctic: the effect of environmental parameters

Abstract: This paper presents a complex study on ciliates from the different species of mosses of King George Island, South Shetland Islands, Antarctic. Samples of ciliates were collected from Polytrichastrum alpinum, Sanionia georgico−uncinata, Sanionia uncinata and Brachythecium austrosalebrosum. The highest species richness (19 taxa) occurred in habitats from Brachythecium austrosalebrosum. The lowest number of taxa (5) was ob− served in Polytrichastrum alpinum. The greatest abundance of ciliates was found in sam− pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Amoebozoa are not reported from MBL, the TM, NVL or the PCM, while Ciliophora are reported from every region except AL and SAP, where the authors of the only studies in these regions exclusively targeted testate amoebae (Decloître 1960(Decloître , 1964Royles et al 2013). These observations reflect the fact that most morphological studies focused exclusively on either testate amoebae (Penard 1911(Penard , 1913Decloître 1960Decloître , 1964Smith 1987;Todorov and Golemansky 1996) or ciliates (Ryan et al 1989;Foissner 1996;Petz andFoissner 1996, 1997;Petz 1997;Mieczan and Tarkowska-Kukuryk 2014;Velasco-Castrillón et al 2014) (Fig. 4).…”
Section: Diversity By Lineage and The Most Widely Distributed Taxamentioning
confidence: 78%
See 1 more Smart Citation
“…Amoebozoa are not reported from MBL, the TM, NVL or the PCM, while Ciliophora are reported from every region except AL and SAP, where the authors of the only studies in these regions exclusively targeted testate amoebae (Decloître 1960(Decloître , 1964Royles et al 2013). These observations reflect the fact that most morphological studies focused exclusively on either testate amoebae (Penard 1911(Penard , 1913Decloître 1960Decloître , 1964Smith 1987;Todorov and Golemansky 1996) or ciliates (Ryan et al 1989;Foissner 1996;Petz andFoissner 1996, 1997;Petz 1997;Mieczan and Tarkowska-Kukuryk 2014;Velasco-Castrillón et al 2014) (Fig. 4).…”
Section: Diversity By Lineage and The Most Widely Distributed Taxamentioning
confidence: 78%
“…(Bamforth et al 2005). In Antarctic moss communities, C. dubium, T. lineare, C. aerophila, A. muscorum, D. lucida and E. rotunda are most frequent and most abundant (Smith 1987;Golemansky and Todorov 2004;Mieczan and Tarkowska-Kukuryk 2014).…”
Section: Phagotrophic Protist Diversity Across Habitat Typesmentioning
confidence: 99%
“…Accordingly, we hypothesized that the diversity of unicellular eukaryotes (protists) would also differ between different microhabitats within tree crowns. So far, molecular studies reported distinct protistan communities in mosses ( Mitchell et al, 2004 ; Mieczan and Tarkowska-Kukuryk, 2014 ), lichens ( Bates et al, 2012 ; Mazei et al, 2016 ), phytothelmata ( Carrias et al, 2001 ; Dunthorn et al, 2012 ) as well as root associated communities ( Turner et al, 2013 ; Dumack et al, 2020 ). Fungal phyllosphere communities determined the community composition of subsequent litter fungal communities ( Guerreiro et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we retain A. limicola and its associated synonyms in this checklist. Due to the difficulty in distinguishing between some Stylonychia species (Haentzsch et al 2006), Mieczan and Tarkowska-Kukuryk (2014) reported a Stylonychia species as Stylonychia mytilus complex, which includes Stylonychia lemnae , Stylonychia mytilus , Stylonychia ammermanni and Stylonychia harbinensis . We include this record due to its ecological significance, even though it is taxonomically incomplete.…”
Section: Discussionmentioning
confidence: 99%